Comparison of three tannases cloned from closely related lactobacillus species: L. Plantarum, L. Paraplantarum, and L. Pentosus - Ueda, Shuhei (BMC Microbiol, 2014)
BACKGROUND: Tannase (tannin acyl hydrolase, EC 3.1.1.20) specifically catalyzes the hydrolysis of the galloyl ester bonds in hydrolyzable tannins to release gallic acid. The enzyme was found not only in fungal species but also many bacterial species including Lactobacillus plantarum, L. paraplantarum, and L. pentosus. Recently, we identified and expressed a tannase gene of L. plantarum, tanLpl, to show remarkable differences to characterized fungal tannases. However, little is known about genes responsible for tannase activities of L. paraplantarum and L. pentosus. We here identify the tannase genes (i.e. tanLpa and tanLpe) of the above lactobacilli species, and describe their molecular diversity among the strains as well as enzymological difference between species inclusive of L. plantarum. RESULTS: The genes encoding tannase, designated tanLpa and tanLpe, were cloned from Lactobacillus paraplantarum NSO120 and Lactobacillus pentosus 21A-3, which shared 88% and 72% amino acid identity with TanLpl, cloned from Lactobacillus plantarum ATCC 14917(T), respectively. These three enzymes could comprise a novel tannase subfamily of independent lineage, because no other tannases in the databases share significant sequence similarity with them. Each of tanLpl, tanLpa, and tanLpe was expressed in Bacillus subtilis RIK 1285 and recombinant enzymes were secreted and purified. The K(m) values of the enzymes on each galloyl ester were comparable; however, the k(cat)/K(m) values of TanLpa for EGCg, ECg, Cg, and GCg were markedly higher than those for TanLpl and TanLpe. Their enzymological properties were compared to reveal differences at least in substrate specificity. CONCLUSION: Two tannase genes responsible for tannase activities of L. paraplantarum and L. pentosus were identified and characterized. TanLpl, TanLpa and TanLpe forming a phylogenetic cluster in the known bacterial tannase genes and had a limited diversity in each other. Their enzymological properties were compared to reveal differences at least in substrate specificity. This is the first comparative study of closely related bacterial tannases.